(untitled) (Revista Apotheke, 2021)
The purpose of this article is to offer contributions to the teaching of arts through the aesthetic theory of John Dewey, performing a thought experiment – ​​narrative that employs fictional literature techniques – which takes place in the form of a drama – a didactic resource that takes the learner to a fictitious scenario in which an educational action takes place. The first section introduces Deweyan theory, emphasizing the concepts of experience, problematic situation, and reflection. The second section presents a drama in which a kindergarten teacher reflects on her experiences with art and seeks a solution to a problem: considering that her own artistic experiences have always been negative, how to teach arts to her students? The article places the teacher inside a thought experiment, in which she learns about Dewey’s theses and gets an answer to her problem. The conclusion of the article suggests that art teachers feel motivated to have experience similar to that of the teacher.